Folk literature for children and youth from the perspective of the Malay mind - Sujud, Arba’ie; Nik Muhamad Affendi, Nik Rafidah; Yaakob, Nor Azuwan; Jusoh, Zuraini (Human Resource Management Academic Research Society, 2021)
Folk tales need to be exposed to children and adolescents. In the Malay folk literature, it was clear that the Malay worldview was reflected. The Malay worldview of life emphasized good relations between human beings, nature, and the environment. This statement proved that the elements found in folk tales could be shared with children and adolescents. Children and teenagers could learn from reading. At this stage of development, children and adolescents began to learn what is right and what is wrong. The objective of this study was to identify the Malay mind found in Children’s and Adolescent Folk Literature and to analyze the Malay mind found in Children's and Adolescent Folk Literature. The findings of the study showed that the folk tales discussed symbolized the wisdom of the mind of the traditional Malay community. Subtly made remarks using natural resources opened the minds of the audience to think.